Pengembangan Job Analysis untuk Pelayanan Pasien BPJS di Rumah Sakit Hermina Mekarsari - Udyanto, Hari Mukti (Jurnal Manajemen, 2019)
The purpose of this paper is to find out the benefits of job analysis in the development of the BPJS patients services in Hospital Hermina Mekarsari. The development oj job analysis is based upon the need to play a role in providing services for the participants of the BPJS. Job analysis based on the needs of those types of job, types of office and character of individuals who perform the task. These results provide broad implication for developing organizational design, compose and projecting future. Labor productivity is increasing due to the creation of the situation and working conditions that are conducive.